Cognitive–behavioural therapy and motivational intervention for schizophrenia and substance misuse - Gillian Haddock; Christine Barrowclough; Nicholas Tarrier; J. Moring; Robert O’Brien; Nichola Schofield; Joanne Quinn; Steven C. Palmer; Linda Davies; Ian Lowens; John McGovern; Shôn Lewis (2003)
Background Comorbid substance misuse in people with schizophrenia is associated with poor clinical and social outcomes. There are few studies of psychological treatments for this population and little long-term follow-up of their benefits. Aims To investigate symptom, substance use, functioning and health economy outcomes for patients with schizophrenia and their carers 18 months after a cognitive–behavioural treatment (CBT) programme. Method Patients with dual diagnosis from a randomised controlled trial of motivational intervention, individual CBT and family intervention were assessed on multiple outcomes at 18-month follow-up. Carers were assessed on symptom, functioning and needs over 12 months. Health economy data were collected over 18 months. Results There were significant improvements in patient functioning compared with routine care over 18 months. No significant differences between treatment groups were found in carer or cost outcomes. Conclusions The treatment programme was superior to routine care on outcomes relating to illness and service use, and the cost was comparable to the control treatment.